Antenatal Care Midwifery Care On Mrs." H" With Chronic Energy Deficiency At The Sorawolio Health Center - Andrika, Ines Febrianti; Anita; Risnawati (International Journal of Multidisciplinary Learners, 2024)
Background: Chronic Energy Deficiency (CHD) is a common nutritional problem experienced by pregnant women, with prolonged lack of energy intake causing CHD. This condition can increase the likelihood of anemia, bleeding, abnormal weight gain, and increase the likelihood of infection which is a risk and complication in pregnant women. The purpose of the preparation of this Final Project Report is to carry out antenatal care midwifery care on Mrs. "H" with chronic energy deficiency at Puskesmas Sorawolio. The subjects in this study were pregnant women, namely Mrs. "H" with chronic energy deficiency at Puskesmas Sorawolio. The method used in this research is a case study with a descriptive approach using Varney’s seven steps and the SOAP intervention method. Results: subjective data: the mother complained of nausea and dizziness that had lasted for 3 days and mild pain in the lower abdomen. Objective data obtained from the examination results showed that the mother’s general condition was good, composmentis consciousness. Blood pressure 120/80 mmHg, pulse 76 x/min, breathing 18 x/min, body temperature 36.7°C. Upper arm circumference 20.7 cm. The management carried out in this case is to encourage the mother to consume food in small portions but often, apply diverse eating habits with nutritious mother’s main food, consume high calorie and protein foods and provide additional food to the mother. Conclusion: The care of Mrs. "H" was carried out in as much detail as possible in accordance with midwifery care and midwifery service standards.